2000
DOI: 10.1088/0953-8984/12/38/301
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostudy of oxygen vacancies in BaTiO3

Abstract: In this paper we present embedded-cluster calculations on singly charged and neutral oxygen vacancies (or F centres) in the oxide perovskite BaTiO3. The simulations include Hartree-Fock theory with MP2 corrections and density-functional-theory calculations for a central quantum defect cluster and a pair-potential description of the embedding lattice. All important defect-induced lattice distortions are taken into account in this way. We discuss the possible electronic states of charged F centres and the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 24 publications
3
45
0
Order By: Relevance
“…24 In SrTiO 3 the singlet ground state is the result of the coupling of the two electrons which occupy 3d(z 2 ) levels on the two Ti atoms. The charge distribution is similar to that found for the same kind of defect in other perovskites like PbTiO 3 , 10 BaTiO 3 , 11 and KNbO 3 .…”
supporting
confidence: 85%
See 2 more Smart Citations
“…24 In SrTiO 3 the singlet ground state is the result of the coupling of the two electrons which occupy 3d(z 2 ) levels on the two Ti atoms. The charge distribution is similar to that found for the same kind of defect in other perovskites like PbTiO 3 , 10 BaTiO 3 , 11 and KNbO 3 .…”
supporting
confidence: 85%
“…6,9,10,11 In this paper we have considered for the first time the competition between magnetic and non-magnetic coupling of the two extra electrons associated with the vacancy. In order to do this, various methods and computational approaches have been adopted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies reveal that the ground state of the singly ionized oxygen vacancy, V · o , involves a transfer of electron density to the 3d 3z 2 −r 2 orbital of the two neighbor axial Ti ions. 56,57 Clustering of the two oxygen vacancies in the form of the axial [V ·· o -Ti 2+ -V ·· o ] ·· complex defect with 2 electrons localized on the Ti 3d 3z 2 −r 2 orbital forming an in-gap electronic state at 0.6 eV below conduction band minimum has been predicted by Cuong et al 58 In a relevant study on Nb-doped SrTiO 3 , Mechelen et al have attributed MIR absorption to the multiphonon sidebands due to the incoherent electron-phonon coupling. 25 They found that the missing Drude spectral weight is nearly recovered in the MIR range.…”
Section: B Mid Infrared Bandmentioning
confidence: 99%
“…On the other hand, several authors reported that the EPR peak with g ≈ 1.97 may be caused by intrinsic Ti 3+ related defects in BaTiO 3 [16][17][18][19][20][21][22][23][24] . A few of them observed this peak just in reduced BaTiO 3 ceramic [20,25]. Some authors whose examinations included EPR spectra at room temperature and above, attributed a peak at g = 1.97 to the localized Ti 3+ states [16].…”
Section: Resultsmentioning
confidence: 99%